(untitled) (American Journal of Development Studies, 2023)
The main objective of this work is to find out the number of labor liabilities for pensions and retirements generated by public servants in federal entities, seeking to answer two questions: What is the amount of labor liabilities owed by local governments up to the year 2021, and what percentage of GDP (state and national) do these amounts represent? This essay was established under the deductive method, in the hermeneutic paradigm, with a quantitative approach. Until 2021, 1.55 million workers working for state governments were recognized, representing 6.5% of formal jobs in the country. From 2009 to 2019, several analyses were carried out indicating that the actuarial liabilities for pensions and retirements of state governments were between 1.38 and 2.2 trillion pesos; this work concludes that the actuarial liabilities of 30 of the 32 federal entities correspond to 4.1 trillion pesos for 2020-2020. 1 trillion pesos for 2020-2021, representing 18.6% of GDP, with the State of Mexico absorbing 22.6%; Mexico City 13.5%; Jalisco 8.1%; Chihuahua 8.2%; Chiapas 5.4%; and San Luis Potosi 4.1%. In contrast, Guanajuato is the best performer in actuarial studies, followed by Aguascalientes, Colima, Hidalgo and Campeche.